Asociación entre nivel de Actividad Física, y Motivación en personas mayores que practican Running (Association between level of Physical Activity and Motivation in older people who practice Running) - Avello-Viveros, Carlos; Ulloa-Mendoza, Rodolfo; Duran-Aguero, Samuel; Carrasco-Castro, Rodrigo; Pizarro-Mena, Rafael (Retos, 2022)
El objetivo del estudio fue asociar el Nivel de Actividad Física y Motivación en Personas Mayores (PM) que practican Running, con variables de Sexo y Edad. Se realizó un estudio observacional de corte trasversal. Se aplicó una encuesta con variables sociodemográficas y experiencias de practicar Running, Escala Rapid Assessment of Physical Activity (RAPA), y Motivations of Marathoners Scales-34 (MOMS-34). Fueron entrevistados 68 corredores PM; 69.2% hombres (n= 47). Según la clasificación RAPA 69.1% eran «Activos»; 49.0% no realizaba ejercicios de fuerza, y 35.0% no realizaba ejercicios de flexibilidad. Al comparar la puntuación media de la parte 1-RAPA por sexos no hubo diferencias significativas; tampoco entre e»70 y <70 años, comparados globalmente como por sexo. En cuanto a la motivación por correr, según las puntuaciones medias de las subescalas de MOMS-34, las principales fueron (3/7): Orientación a la Salud, Significado de la Vida-Autoestima, Superación de metas Personales-Competición. Al comparar las puntuaciones medias de las subescalas MOMS-34 según sexo, no hubo diferencias significativas; al comparar entre e»70 años y <70 años, existió diferencias significativas en la subescala de Afiliación (p<.05). Al comparar según edad y sexo, en hombres, existió diferencias significativas en subescala de Afiliación y Peso (p<.05), y no hubo diferencias en mujeres. Como conclusión, 2/3 de las PM corredores entrevistados posee nivel físico «Activo», sin diferencias significativas entre sexos y edad; y las mayores motivaciones para realizar Running son Orientación a la salud, Significado de la vida-Autoestima, Superación de Metas Personales-Competición, sin diferencias por sexo, si en hombres según edad. Abstract. The objective of the study was To associate the Level of Physical Activity and Motivation in Older People (OP) who practice Running, with variables of Sex and Age. An observational cross-sectional study was carried out. A survey was applied with sociodemographic variables and experiences of practicing Running, Rapid Assessment of Physical Activity Scale (RAPA), and Motivations of Marathoners Scales-34 (MOMS-34). 68 PM runners were interviewed; 69.2% men (n= 47). According to the RAPA classification, 69.1% were «Active»; 49.0% did not perform strength exercises, and 35.0% did not perform flexibility exercises. When comparing the mean score of part 1-RAPA by gender, there were no significant differences; nor between e»70 and <70 years, compared globally and by sex. Regarding the motivation to run, according to the mean scores of the MOMS-34 subscales, the main ones were (3/7): Health Orientation, Meaning of Life-Self-esteem, Overcoming Personal Goals-Competition. When comparing the mean scores of the MOMS-34 subscales according to gender, there were no significant differences; When comparing between e»70 years and <70 years, there were significant differences in the Affiliation subscale (p<.05). When comparing according to age and sex, in men, there were significant differences in the Affiliation and Weight subscale (p<.05), and there were no differences in women. In conclusion, 2/3 of the PM runners interviewed have an «Active» physical level, with no significant differences between sexes and age; and the greatest motivations for Running are Health orientation, Meaning of life-Self-esteem, Overcoming Personal Goals-Competition, without differences by sex, if in men according to age.